Human-centered design of a privacy assistant and its impact on perceived transparency and intervenability - Kiss Lennart; Sellung Rachelle (i-com)
This paper showcases a user study on users’ preferences and perceptions of data protection (e.g., intervenability and transparency) in a privacy assistant application. The tool aims to assist users in maintaining higher data protection of their personal data with minimal effort. The study involved 20 participants and employed a mixed-methods approach, including qualitative analysis to assess user perceptions and usability. The findings of the study are two-fold, (1) to understand the user requirements and attitudes towards data protection and privacy and (2) to evaluate whether the privacy assistant application meets these requirements in terms of transparency, intervenability, user experience, and usability. The results indicate that participants had varying attitudes toward privacy and exhibited diverse knowledge levels regarding the GDPR. The high-fidelity prototype demonstrated excellent usability and received positive evaluations in terms of user experience across various dimensions. The results shed light on both the strengths and areas for improvement in the design and implementation of the privacy assistant application prototype.